Analysis of the Causes and Efforts to Protect Child Labor from an Indonesian Legal Perspective - Intan Maharani; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
Children's age is a golden age that should not be burdened with things that hinder development and growth both from social, physical, mental and spiritual aspects. Their job at that age is just to learn and play. The phenomenon that occurs is that many children are burdened with heavy work which hinders all their development and potential. The importance of children's existence for the survival of a nation encourages the government to establish a set of regulations in an effort to protect children. Despite this, the fact is that the problem of child labor is still a serious problem, especially in Indonesia. This article aims to analyze and determine the causes and legal protection efforts for child labor based on the laws in force in Indonesia. This article concludes that firstly, the determinants of child labor problems are influenced by various factors that are interrelated with each other, namely poverty factors, educational factors, urbanization, social culture, changes in production processes and weak supervision. Second, from a review of the legal protection of child labor from the legal perspective in force in Indonesia, it is very strong, where there are many laws and regulations that guarantee it, but in terms of practice or implementation, it is still very weak. The laws referred to include Law Number 1 of 2000 concerning the ILO convention, Law number 13 of 2003 concerning employment, Law number 20 of 1999 concerning ratification of the ILO convention, Law Number 35 of 2014 concerning child protection and Law Number 11 of 2012 concerning the Juvenile Justice System and many other laws and regulations that are in line with this law.